KELOLAAN PEMBIAYAAN DAN PORTOFOLIO PEMBIAYAAN BERMASALAH DAMPAKNYA TERHADAP PENGELOAAN TOTAL ASSET PADA PT. BANK MUAMLAT INDONESIA - Agus Supriatna; Janudin Janudin; Oki Ikbal Khair (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This research was carried out to find out whether there was a significant impact of managed financing and non-performing financing portfolios on the management of total assets at PT Bank Muamalat Indonesia in 2009 to 2018 either partially or simultaneously. This type of research is descriptive quantitative using secondary data types obtained from the Publication Financial Statements of PT Bank Muamalat Indonesia or BMI from the Bank's Annual Report, from 2009 to 2018. The data analysis method uses classical assumption test techniques and Linear Regression Analysis techniques , Correlation Coefficient test, partial hypothesis test (t test), simultaneous test (F test) and Coefficient of Determination test with the variable Financing Management (X1) and Non-Performing Financing Portfolio (X2) and Total Asset Management at PT Bank Muamalat Indonesia as a variable (Y). The tests were carried out using the SPSS For Windows version 20 application. The results obtained with the multiple regression equation PTA = - 2,314,464,26 + 1,33KP + 1,93NPF and with the results of the Simultaneous Test the value of Fcount 3.978 < Ftable 4.74 with table significance value of 0.070 from the value of the significance level = 0.05. So that simultaneously the Financing Management (KP) and Non-performing Financing Portfolio (NPF) simultaneously have no significant effect on Total Asset Management at PT Bank Muamalat Indonesia. The value of Adjusted R-Square (R2) is 0.532 or (0.532 x 100% = 53.20%) this shows that although there is no significant effect, there is a contribution of KP and NPF variables to the PTA variable of 58.20% while 46, 80% by other factors